Foundations of Brazilian economic growth - Syvrud, Donald E.; American Enterprise Institute for Public Policy Research (Stanford, Calif. : Hoover Institution Press, Stanford University, 1974)
This book contains a number of important lessons for both the developing countries that are seeking to promote economic growth and social development, and for the developed countries, including the United States, that are struggling with the dilemma of inflation and unemployment.
Includes index.
Includes bibliographical references: p. 277-281 and index.
hza 28/01/2019
Loans
Keywords: Economic growth; Brazil; Brazil